Jump height from inertial recordings: A tutorial for a sports scientist - Rantalainen, T.; Finni, T.; Walker, S. (Scandinavian Journal of Medicine & Science in Sports, 2020)
Jump performance provides meaningful information both for sporting and clinical needs. Current state of the art in jump performance assessment is laboratory-bound; however, out-of-the-laboratory methods are desirable. Therefore, the purposes of the present investigation were (a) to explore whether utilizing a novel analytical approach minimizes the bias between inertial recording unit (IMU)-based and jump mat-based jump height estimates and (b) to provide a thorough tutorial for a sport scientist (see Appendix S1) to facilitate standardization of jump height estimation. Forty-one women, men, and boys aged 6 to 77 years completed three maximal countermovement jumps without arm swing, which were concurrently registered with a jump mat, and an IMU worn in low lumbar region. Excellent agreement between the novel IMU-based jump height and jump mat jump height was observed (mean IMU 22.6 [8.3] cm, mean jump mat 22.7 [8.9], mean bias -0.1 cm [95% limits of agreement -4.5 cm to 4.4 cm; P = .826], and intra-class correlation coefficient 0.97 [95% CI 0.94 to 0.98, P < .001]). In conclusion, inertial recordings conducted with lightweight IMUs worn on the hip provide a valid and feasible assessment of jump height among people with varying athletic ability. Inertial signals have the potential to afford (at least semi-) automated analysis pipeline with low labor cost thus being potentially feasible in applied settings such as in professional sports or in the clinics.